RESISTANCE LITERATURE IN THE 50S - 80S OF THE XX CENTURY - Khusenova Mehriniso Uktamovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The literature of the 20th century is full of war, and this leaves its mark on those books where the war is not directly depicted. It is wrong to think that only decadents or authors of detective novels write about death and murder. Almost all realist literature of our time is filled with death. Comparing it with the great classical literature of the West, one can easily see that the modern writer more often approaches the depiction of a person from a different angle: finding out the moral character of his hero, he does not so much draw his life as he confronts him with the problem of non-existence.